Association between Serum Zinc Level and Cutaneous Viral Warts - صفيه هدى; محمد اسماعيل; يوسف زريق (Latakia University Journal -Medical Sciences Series, 2023)
Background: Warts are benign tumors of the skin and mucosa caused by Human papilloma viruses (HPVs), leading to a slow and focal expansion of squamous epithelial cells. They are clinically visible as well defined hyperkeratotic protusions. Zinc is an essential trace element has immunomodulatory effects that could counteract viral infections. Some researchers have reported an association between low serum zinc level and cutaneous viral warts. Aim: To evaluate serum zinc level in patients with warts in comparison with its level in age and sex-matched healthy controls. Materials and Methods: This case- control study included (62) patients with warts and (26) control subjects. Serum zinc level was determined using colorimetric method. Comparison of mean serum zinc level was done between groups of patients and controls. Association between serum zinc level and each of sex, age, number of lesions, type of lesions, duration of infection, and recurrence was also evaluated in all patients. Results: Serum zinc level was significantly lower in patients with warts than control individuals (98.86±12.3 μg/dl and 124.03±9.05 μg/dl respectively, p-value=0.0001). Significant inverse correlation existed between serum zinc level and both the number of lesions and the duration of infection. Also there was significant association between serum zinc level and both the sites of lesions and recurrence. In contrast, no significant association was found between serum zinc level, sex, age or the type of lesions. Conclusion: Lower serum zinc level existed in patients with warts and significant association with severity of disease was observed. This suggests a possible role of zinc in the pathogenesis of warts. Accordingly, zinc supplements may provide a therapeutic benefit.